A woman's struggles in facing a new environment in Anne of Green Gables: A sociological approach - Wulandari, Erina Eka; Wajiran, Wajiran (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This paper examines the theme of adaptation and identity formation in L.M. Montgomery's Anne of Green Gables, focusing on the character of Anne Shirley and her resilience in the face of social exclusion and adversity. The study aims to explore how Anne’s personal growth is shaped by external societal pressures and how her imagination serves as a coping mechanism to overcome these challenges. This paper uses Durkheim’s theory of social facts and C. Wright Mills’ concept of sociological imagination to analyze how Anne’s interactions with the Avonlea community reflect broader social integration, conformity, and individual agency issues. The method employed is a close textual analysis of Anne’s character development, focusing on her social environment and internal psychological strategies. By applying sociological frameworks, the study situates Anne’s struggles within a larger context of social pressures and adaptation.The findings suggest that Anne’s resilience, imagination, and intelligence allow her to navigate an initially hostile environment, leading to her eventual acceptance in Avonlea. The paper concludes that Anne of Green Gables offers enduring insights into the complexities of social adaptation and personal identity, making it relevant to contemporary discussions on resilience and societal expectations.